Bispectral index for improving anaesthetic delivery and postoperative recovery - Yodying Punjasawadwong (2018)
© 2017 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. Background: The use of clinical signs may not be reliable in measuring the hypnotic component of anaesthesia. The use of bispectral index (BIS) to guide the dose of anaesthetic may have certain advantages over clinical signs. This is the second update of a review originally published in 2007 and updated in 2014. Objectives: The primary objective of this review focused on whether the incorporation of BIS into the standard practice for management of anaesthesia can reduce the risk of intraoperative awareness, consumption of anaesthetic agents, recovery time and total cost of anaesthesia in surgical patients undergoing general anaesthesia. Search methods: In this updated version, we searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2013, Issue 1), MEDLINE (1990 to 31 January 2013), Embase (1990 to 31 January 2013) and reference lists of articles. Previously, we searched to May 2009. We reran the searches on 27 February 2017. We identified 14 potential new studies of interest which were added to a list of 'Studies awaiting Classification' and will be incorporated into the f ormal review findings during the review update. In total there are 17 studies awaiting classification. Selection criteria: We included randomized controlled trials comparing BIS with standard practice criteria for titration of anaesthetic agents. Data collection and analysis: Two authors independently assessed trial quality, extracted data and analysed the data. We contacted study authors for further details. Main results: We included 36 trials. In studies using clinical signs as standard practice, the results demonstrated a significant effect of the BIS-guided anaesthesia in reducing the risk of intraoperative awareness among surgical patients at high risk for awareness (7761 participants; odds ratio (OR) 0.24, 95% confidence interval (CI) 0.12 to 0.48). This effect was not demonstrated in studies using end tidal anaesthetic gas (ETAG) monitoring as standard practice (26,530 participants; OR 1.13, 95% CI 0.56 to 2.26). BIS-guided anaesthesia reduced the requirement for propofol by 1.32 mg/kg/hr (672 participants; 95% CI -1.91 to -0.73) and for volatile anaesthetics (desflurane, sevoflurane, isoflurane) by 0.65 standardized mean difference of minimal alveolar concentration equivalents (MAC SMD equivalences) (95% CI -1.01 to -0.28) in 985 participants. Irrespective of the anaesthetics used, BIS reduced the following recovery times: time for eye opening (2557 participants; by 1.93 min, 95% CI -2.70 to -1.16), response to verbal command (777 participants; by 2.73 min, 95% CI -3.92 to -1.54), time to extubation (1501 participants; by 2.62 min, 95% CI -3.46 to -1.78), and time to orientation (373 participants; by 3.06 min, 95% CI -3.63 to -2.50). BIS shortened the duration of postanaesthesia care unit stay by 6.75 min (1953 participants; 95% CI -11.20 to -2.31) but did not significantly reduce the time to home readiness (329 participants; -7.01 min, 95% CI -30.11 to 16.09). Authors' conclusions: BIS-guided anaesthesia can reduce the risk of intraoperative awareness in surgical patients at high risk for awareness in comparison to using clinical signs as a guide for anaesthetic depth. BIS-guided anaesthesia and ETAG-guided anaesthesia may be equivalent in protection against intraoperative awareness but the evidence for this is inconclusive. In addition, anaesthesia guided by BIS kept within the recommended range improves anaesthetic delivery and postoperative recovery from relatively deep anaesthesia.